2003
DOI: 10.1074/jbc.m304667200
|View full text |Cite
|
Sign up to set email alerts
|

Biological Activities of Homologous Loop Regions in the Laminin α Chain G Domains

Abstract: Laminin ␣ chains (␣ 1 -␣ 5 chains) have diverse chainspecific biological functions. The LG4 modules of laminin ␣ chains consist of a 14-stranded ␤-sheet (A-N) sandwich structure. Several biologically active sequences have been identified in the connecting loop regions. Here, we evaluated the biological activities of the loop regions of the E and F strands in the LG4 modules using five homologous peptides from each of the mouse ␣ chains (EF-1: DYATLQLQEGRLHFMFDLG, ␣ 1 chain 2747-2765; EF-2: DFGTVQLRNGFPFFSYDLG,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
128
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 79 publications
(143 citation statements)
references
References 57 publications
9
128
0
6
Order By: Relevance
“…EF-1 is located on the E and F strand and the connecting loop region. We synthesized cyclic-EF-1 and found that cyclic-EF-1 had stronger cell adhesive activity than linear EF-1 (17). It is possible that cyclic-A2-8 may promote strong cell attachment activity and enhance the specificity of integrin ␣2␤1 binding more potently than the linear A2-8 peptide.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…EF-1 is located on the E and F strand and the connecting loop region. We synthesized cyclic-EF-1 and found that cyclic-EF-1 had stronger cell adhesive activity than linear EF-1 (17). It is possible that cyclic-A2-8 may promote strong cell attachment activity and enhance the specificity of integrin ␣2␤1 binding more potently than the linear A2-8 peptide.…”
Section: Discussionmentioning
confidence: 99%
“…3). AG73, which interacts with syndecans and promotes heparin-dependent cell attachment, and EF-1, which interacts with integrin ␣2␤1 and promotes a divalent cation-dependent cell adhesion (17), were used as controls. To evaluate the inhibitory effect of EDTA and heparin on cell adhesive peptides on the 96-well plates, A2-20 was conjugated with a chitosan membrane in the well.…”
Section: Peptides From the N-terminal Region Of Mouse Laminin ␣2mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, we previously identified about sixty cell-adhesive sequences from laminin-111 using 673 synthetic peptides covering the entire sequence. These active peptides promote various biological activities, including the promotion of cell spreading, cell differentiation, neurite outgrowth, angiogenesis and wound healing, and many of them bind to distinct cellular receptors [32][33][34][35]37,38].…”
Section: Introductionmentioning
confidence: 99%